PERAN BADAN PERTANAHAN DALAM MEREDUKSI KONFLIK DAN PERKARA SENGKETA TANAH MELALUI MEDIASI - Mega Puspa Kusumojati; Abraham Ferry Rosando; Tomy Michael (COURT REVIEW, 2021)
This research seeks to discuss the role of the National Land Agency in reducing land disputes and conflicts through mediation. A dispute refers to a public statement regarding a claim that is inconsistent with something of value. Meanwhile, a conflict refers to disagreement which is macro in nature, for example, a conflict between communities or groups. Based on the Regulation issued by the Ministry of Agrarian Affairs/Spatial Planning, there is a statement about institutions. This invokes vagueness of norms which is not clearly regulated concerning what kind of dispute and conflict falls under the authority of other institutions, resulting in another interpretation found in Article 11 paragraph (4) of the Regulations of the Ministry of Agrarian Affairs/Spatial planning Number 11 of 2016 concerning the settlement of land disputes which are not under the authority of the ministry. The process of resolving land disputes by the National Land Agency as a mediator as stated in the Regulation of the Ministry of AgrarianAffairs Number 11 of 2016 concerning the settlement of land disputes, mediation for disputes, and conflict resolution based on reports from the Administration section at the National Land Agency is categorized into two types; by the Ministry initiative and by the public complaint. Efforts made by the Ministry of Agrarian Affairs/ Land Agency can be in form of evaluation and review towards the Regulation of the Ministry of Agrarian Affairs/Spatial planning Article 11 paragraph (4) which can be applied according to community needs which specifically does not cause misinterpretation in resolving disputes and conflicts. From the community perspective, lawsuits take a long time and cost a lot of money. Therefore, mediation by the National Land Agency using a persuasive approach and focusing on a win-win solution for both parties based on the principle of justice is preferred.